Who Participates in Content-Focused Teacher Professional Development? Evidence From a Large Scale Study - Richter, Eric; Kunter, Mareike; Marx, Alexandra; Richter, Dirk (Frontiers in Education, 2021)
This study investigates the relationship between teacher quality and teachers’ engagement in professional development (PD) activities using data on 229 German secondary school mathematics teachers. We assessed different aspects of teacher quality (e.g. professional knowledge, instructional quality) using a variety of measures, including standardised tests of teachers’ content knowledge, to determine what characteristics are associated with high participation in PD. The results show that teachers with higher scores for teacher quality variables take part in more content-focused PD than teachers with lower scores for these variables. This suggests that teacher learning may be subject to a Matthew effect, whereby more proficient teachers benefit more from PD than less proficient teachers.